The restoration of physical and mechanical properties of wheel rim metal - Somov, Dmitrij; Bazaras, Žilvinas (Transport, 2011)
Despite reduced resistance to wheel rim wear, after every grinding, only geometrical parameters of wheels are restored at maintenance depots. A tendency towards a decrease in the exploitation of wheel rim working edge induces the acquisition of new wheels, is related to a considerable increase in axle load and train speed as well as linked to the ineffective methods of repairing wheel rim working edge. A solution to the problem of restoring the surface of wheelset rolling, as a wider problem of rolling stock durability, is determined by the fact that the breakdown of the rolling wheelset and the loss of its efficiency shortens the service time of the wheelset. The cost of pointless and inefficient renovations of geometrical wheelset parameters increases and is of a very high rate. The problem of efficient renovations to rims and steel used for wheels within the maintenance of wheelsets becomes a burning issue today.First Published Online: 05 Oct 2011